Major factors affecting the closure of marine carbonate caprock and their quantitative evaluation: A case study of Ordovician rocks on the northern slope of the Tazhong uplift in the Tarim Basin, western China. (May 2017) - Lü, Xiuxiang; Wang, Yafang; Yu, Hongfeng; Bai, Zhongkai
Abstract: There are many examples of oil and gas reservoirs throughout the world that have tight carbonate rock as the caprock. These oil and gas reservoirs are often vertically overlapped (with multiple oil and gas sections) and laterally connected (to many oil and gas reservoirs). The closure of carbonate caprock is affected by many factors, such as the clay content, differential diagenesis and layer thickness. As evaluation parameters, the clay content can be determined by a gamma ray well-logging curve; the differential diagenesis is reflected in filling effects, rupture effects, cement composition and content and can be measured through the displacement pressure; the layer thickness can be obtained from drilling and well-logging data. In different regions or different members, the factors and parameters to be considered or evaluated for the closure are dependent on actual geological conditions. In this study, the clay content, displacement pressure and layer thickness were analysed, determined, calculated and normalized to generate an overall closure evaluation index (λ) for the caprock in wells on Ordovician Liang 3–5 mud-bearing limestone members on the northern slope of the Tazhong uplift. On the plane distribution map, the area with λ ≥ 1 was effectively sealed. The tight carbonate in the inner Yingshan Formation (with high-resistivity, referred to as a high-resistivity layer) was also effectively caprock. Regardless of whether it can seal oil and gas, the sealing capacity mainly depends on the displacement pressure difference between the high-resistivity layer and the underlying carbonate reservoir. Based on drilling results and the comparison of the displacement pressure difference between the two layers (by actual measurements and calculations), we observed that when the pressure difference is more than 1.95 MPa, it is an effective caprock. Highlights: A large scale of tight carbonate rock can seal hydrocarbon. λ can evaluate sealing capacity of mud-bearing tight carbonate rock. (λ indicates the comprehensive evaluation index). ΔP can evaluate sealing capacity of pure tight carbonate rock. (ΔP indicates the displacement pressure difference).